Separatism as an Ethno-Political Conflict: Threats to Ukraine and Challenges for Poland - Михайло Мосора (Історико-політичні проблеми сучасного світу)
The purpose of the author's research is to consider the threats to Ukraine and Poland of separatism. The author defines the following tasks: definition of the concept of separatism, analysis of modern threats of ethno-political conflicts in the EU, Poland and Ukraine, etc. The article analyzes the peculiarities of autonomism and separatism manifestations as political conflicts. The peculiarities of political conflicts in the EU democratic societies, particularly, in the Republic of Poland are singled out. The examples of similar conflict situations in the EU are provided. The possible issues of ethnonational conflicts in the EU in the future are revealed. Author mention that separatism exists in the EU most often in the state of static balance. The necessity is proved to address the issues of community identification through the prism of dual identification. The article substantiates the importance of current favorable factors of regionalization in the EU to enhance identification and politicization of regional ethnic groups in the European countries, particularly, in Poland and Ukraine. In author view, the main features of separatism are presence of conflicts between different groups in the context of the identity plurality of the political structure, communities’ intolerance of the concept of dual identity proposed by the central government, etc.